Conflict Resolution In Sudan And Its Impacts On The International Scale - Khairunnisa, Brilliant Windy (El Tarikh : Journal of History, Culture and Islamic Civilization, 2023)
Sudan has always been known for the hostilities that took place there, long before Sudan was divided into Sudan and South Sudan. Both internal and international conflicts involve several countries. After the separation of South Sudan, Sudan began to experience internal conflicts related to the struggle for state power in overthrowing President Omar al-Bashir. However, after the overthrow of the president, a new conflict emerged to seize power between the two camps that had previously collaborated in overthrowing the previous president. This study aims to explore how the current conflict resolution in Sudan and how it impacts on an international scale. Through exploratory qualitative research methods, this study presents primary and secondary data resulting from interviews and literature studies. This study provides information on the current Sudan conflict with its potential resolution as well as some impacts on a global scale.Keywords: Conflict Resolution, Current Sudan Conflict, Impact, International Scale.